2016
DOI: 10.1186/s12906-016-1261-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the pulsed electromagnetic field PST® on human tendon stem cells: a controlled laboratory study

Abstract: BackgroundCurrent clinical procedures for rotator cuff tears need to be improved, as a high rate of failure is still observed. Therefore, new approaches have been attempted to stimulate self-regeneration, including biophysical stimulation modalities, such as low-frequency pulsed electromagnetic fields, which are alternative and non-invasive methods that seem to produce satisfying therapeutic effects. While little is known about their mechanism of action, it has been speculated that they may act on resident ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 34 publications
0
16
1
Order By: Relevance
“…The medium was changed every 2-3 days. All experiments were carried out with cells at passage four to six after isolation [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The medium was changed every 2-3 days. All experiments were carried out with cells at passage four to six after isolation [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…All photomicrographs were acquired with an Axiovert 40 microscope (Zeiss) equipped with a Moticam 2300 camera (Motic). The mRNA expression of adipogenic markers including PPAR- γ and LPL were also assessed on days 7 and 21 by real-time PCR, as described above [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…Surprisingly, TSPCs electromagnetically stimulated (30 Hz, 1.5 mT) for 60 min presented a similar migratory profile compared to unexposed cells (Randelli et al, ). In this study, authors also reported that electromagnetic stimulation is likely to maintain TSPCs in an undifferentiated state by regulating stem cell reprogramming factors octamer‐binding transcription factor 4 (Oct4), Kruppel‐like factor 4 (KLF4) and Nanog, up to 48 hr following stimulation (Randelli et al, ).…”
Section: Beyond Repair: Shooting For Regenerationmentioning
confidence: 96%
“…Surprisingly, TSPCs electromagnetically stimulated (30 Hz, 1.5 mT) for 60 min presented a similar migratory profile compared to unexposed cells (Randelli et al, ). In this study, authors also reported that electromagnetic stimulation is likely to maintain TSPCs in an undifferentiated state by regulating stem cell reprogramming factors octamer‐binding transcription factor 4 (Oct4), Kruppel‐like factor 4 (KLF4) and Nanog, up to 48 hr following stimulation (Randelli et al, ). In a different study, tendon‐derived cells stimulated with low‐frequency static magnetic field (2 Hz, 350 mT) had enhanced expression of COL1A1, TNC, DCN, and SCX after a single exposure for 8 hr (Pesqueira, Costa‐Almeida, & Gomes, ).…”
Section: Beyond Repair: Shooting For Regenerationmentioning
confidence: 96%
“…The use of magnetic forces in tissue healing is quite recent and some pioneer studies suggest the in uence of magnetic elds in modulating tendon injury recovery after rat Achilles transection (Strauch et al 2006). Besides pain relief (Nelson eta l. 2013) and stimulation of blood circulation, magnetotherapy has been reported to stimulate tendon cell proliferation (Seeliger et al 2014, Randelli et al 2016 in the promotion of the healing process.…”
Section: Magnetic Stimulationmentioning
confidence: 99%